(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
This article will examine two of the world’s emerging middle powers Brazil and South Africa, the rise and promulgation of their cooperative strategies to reform institutions such as the United Nations Security Council. The article tries to examine the instrumental nature of South African and Brazilian foreign policy within the framework of both countries’ commitment to multilateralism and if this has been rising as part of a new form of shallow multilateralism or a regenerated regionalism of the South. Moreover, with regards to recent crises in Honduras and Zimbabwe, we will try to offer a critical evaluation of both countries global standing and their effort to promote democratic values in regional and sub-regional levels.